COMPARISON OF LED PHOTO-THERAPY WITH CONVENTIONAL PHOTOTHERAPY IN THE TREATMENT OF HYPERBILIRUBINEMIA IN NEONATES IN TERMS OF SAFETY AND EFFECTIVENESS - Junaid Ahmed; Komal Atta; Sadia Zafar et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:BACKGROUND: neonatal jaundice is a commonly occurring cause of severe brain damage if not eﬀectively treated and diagnosed. OBJECTIVE: To compare the eﬀects of LED phototherapy with conventional phototherapy in treatment of unconjugated neonatal jaundice in terms of mean duration of phototherapy, drop in total serum bilirubin levels and side eﬀects observed by the treatment modalities.METHODS: A randomized control trial was conducted in the department of Pediatrics, D.H.Q Hospital, Faisalabad. 140 neonates, aged between 2-28 days of both genders having unconjugated jaundice were included in the study. All the children were divided into two groups. Patients received LED phototherapy in group A and conventional phototherapy in group B. Data was subjected to percentages, chi square tests, frequency for qualitative and independent t tests for non-qualitative variables on the statistical package for social sciences (SPSS) software, version 22. RESULTS: Out of 140 patients, mean age of the patients in gestational weeks was 35.44±7.36. 77(55%) patients were male while 63(45%) patients were female. Mean duration of phototherapy in group A and B were 48.1±24.1 hours and 96.3±33.2 hours respectively (p-value=0.0001). The rates of fall of TSB were 0.45[SE = 0.03] and 0.10 [SE = 0.01] mg/dL/hour in the LED and ﬂuorescent groups, respectively (P = 0.472)2(2.9%) patients had hyperthermia in group A while 10(14.3%) patients had hyperthermia in group B (p-value=0.016).CONCLUSION: LED phototherapy is more advantageous over the conventional method for the treatment of unconjugated neonatal jaundice, in terms of duration, safety proﬁle and also it results in lesser degree of hyperthermia.